Ethnobotanical Study of Magar Ethnic Community of Palpa District of Nepal - Pangeni, Bimala; Bhattarai, Shandesh; Paudyal, Hari; Chaudhary, Ram Prasad (Ethnobotany Research and Applications, 2020)
Background: This study was aimed to document the important medicinal plants and their herbal preparation method. The investigation and documentation of medicinal plants and their associated indigenous knowledge are crucial to raise the socio-economic status of the indigenous Magar ethnic community, and for the conservation of biological resources. Methods: Participatory Rural Appraisal (PRA) that involved direct interaction with local people and observations was used to collect data. Informant Consensus Factor (Fic) and Relative Frequency Citation (RFCs) were applied to explore the cultural importance of ethnomedicinal plants. Results: Forty medicinal plants, out of 58 ethnobotanically useful plant species were reported. Fic value was found to be high (1) for treatment of maternal ailment, followed by eye irritation (0.95), rheumatism and urinary ailments (0.92). Similarly, cancer (0.90), skin diseases (0.87), asthma (0.83), nervous system disorders (0.73), fever (0.67), gastrointestinal (0.53), and least value was recorded for respiratory problems (0.48). Based on the RFCs values, the most important ethnomedicinal species were Cissampelos pariera (0.86), Centella asiatica (0.78), Bergenia ciliata (0.54), Delphinium vestitum (0.48), Clematis buchananiana (0.44), Oxalis corniculata (0.42), Cassia fistula (0.32), Cuscuta reflexa and Asparagus racemosus (0.26), Corchorus aestuans (0.24), and Nicotiana tabacum (0.22). Conclusions: Further research on high valued plants for investigation of particular chemical components and their commercialization into national level is recommended. Results on such aspects would help local communities to conserve and disseminate their ethnomedicinal knowledge, and also to transfer their unique healthcare practices to young generations. Keywords: Indigenous knowledge, Magar ethnic community, Medicinal practices, Palpa District